Role of Leptin in the Association Between Body Adiposity and Persistent Asthma: A Longitudinal Study. Issue 6 (20th April 2019) - Li, Zhen; Leynaert, Bénédicte; Dumas, Orianne; Diaz Gil, Oscar; Garcia‐Aymerich, Judith; Fito Colomer, Montserrat; Le Moual, Nicole; Pison, Christophe; Romieu, Isabelle; Siroux, Valérie; Camargo, Carlos A.; Varraso, Raphaëlle; et al.
Abstract : Objective: Obesity is a likely risk factor for asthma. However, underlying mechanisms by which obesity affects asthma activity remain poorly understood. This study aimed to investigate the role of leptin, an adipocyte‐derived proinflammatory protein, as a mediator in the association between body adiposity (assessed using BMI, waist circumference, and body fat percentage) and persistent asthma. Methods: A causal approach to mediation analysis was used to disentangle total and direct effects and the indirect effect mediated by leptin, using data from the French prospective French Epidemiological Study on the Genetics and Environment of Asthma (EGEA) (baseline: 2003‐2007; follow‐up: 2011‐2013; mean follow‐up time: 7 years). A total of 331 participants with current asthma at baseline were included. Results: Per 1‐SD increment in BMI, waist circumference, and body fat percentage, the adjusted odds ratios of the total effect were 1.59 (95% CI: 0.95‐2.97), 2.06 (1.06‐4.00), and 3.25 (1.01‐9.41), respectively; the odds ratios of the indirect effect mediated by leptin were 1.68 (1.09‐2.46), 1.55 (0.99‐2.57), and 1.99 (0.94‐4.83), respectively. Conclusions: Leptin partly (> 60%) mediated the association between high body adiposity and persistent asthma over time. Using a newly developed analytic approach, this longitudinal study brought new insight into one mechanism by which obesity may affect asthma activity.